Engineering Fundamentals : An Introduction to Engineering - Moaveni, Saeed, author (Australia ; United States, Boston : Cengage Learning, 2016)
Introduction to the engineering profession -- Preparing for an engineering career -- Introduction to engineering design -- Engineering communication -- Engineering ethics -- Fundamental dimensions and units -- Length and length-related variables in engineering -- Time and time-related variables in engineering -- Mass and mass-related variables in engineering -- Force and force-related variables in engineering -- Temperature and temperature-related variables in engineering -- Electric current and related variables in engineering -- Energy and power -- Computational engineering tools electronic spreadsheets -- Computational engineering tools MATLAB -- Engineering drawings and symbols -- Engineering materials -- Mathematics in engineering -- Probability and statistics in engineering -- Engineering economics.